EPEN-18. TRANSCRIPTOMICS SEQUENCING REVEALS ABERRANT ALTERNATIVE SPLICING IN RECURRENT POSTERIOR FOSSA EPENDYMOMAS. Issue 2 (22nd June 2018) - Lourdusamy, Anbarasu; Ritzmann, Timothy; Rogers, Hazel; Donson, Andrew; Chapman, Rebecca; Storer, Lisa; Jacques, Thomas; Paine, Simon; Foreman, Nicholas; Grundy, Richard
Abstract: Ependymoma is the second most common posterior fossa tumour in children and causes significant neurological morbidity and mortality. Although these tumours are morphologically similar, recent advances in genomics have revealed that posterior fossa ependymoma (PF-EPN) is actually comprised of three distinct biological entities. Despite these differences, PF-EPN commonly resists chemotherapy and majority of them will recur. Recurrent ependymoma is fatal in children, and yet little is known about its biology. We hypothesized that post-transcriptional changes such as alternative splicing could reveal the underlying mechanisms and uncover genes that would inform actionable targets for therapy. To this end, we mapped the alternative splicing landscape in 17 matched paired samples of primary-recurrent PF-EPNs in children using RNA-seq. We identified 582 differential alternative splicing (AS) events between primary and recurrent PF-EPN, covering five basic types of AS patterns with cassette exon skipping being the majority of the AS events affected (~ 63%). These AS events were enriched for cancer hallmarks important for sustained proliferation and invasion, and affecting key regulators of invasive phenotype such as CD44 and TNC. In addition, immune system genes were enriched among AS events that show shift in inclusion levels in recurrent PF-EPN. Strikingly, genes with AS events did not show significant expression changes between primary and recurrent PF-EPN at the whole-transcript level, suggesting, AS events are an independent and informative measure for defining recurrent ependymoma. Collectively, our data provides evidence for widespread splicing dysregulation in PF-EPN, and suggests the role of aberrant AS in the pathogenesis of ependymoma.